QUALITY OF LIFE AND SOCIETY 5.0 - Slavko Arsovski (Proceedings on Engineering Sciences, 2019)
In Japan is process for achieving a "Super-Smart Society" as fifth stage of society`s development. It is natural extension of today's Information Society (Fourth stage) wich includes Germany's "Industry 4.0" vision. Through analysis elements of Society 5.0 are emphasized four main carracteristics: (1) optimising society as a whole with integration of cyber space and physical space, (2) using data as a new resource, (3) realising in environment with change and constraints, and (4) solving complex social and living problems. All of them and esspecialy the last one is related to Quality of Life (QoL). In the paper are presented structure and requests related to Society 5.0, as well as new model of QoL and relationships among them.